Local constructions of gender-based violence amongst IDPs in northern Uganda: analysis of archival data collected using a gender- and age-segmented participatory ranking methodology - Alastair Ager; Carolyn Bancroft; Elizabeth Berger; Lindsay Stark (Conflict and Health, 2018)
Abstract Background Gender-based violence (GBV) is a significant problem in conflict-affected settings. Understanding local constructions of such violence is crucial to developing preventive and responsive interventions to address this issue. Methods This study reports on a secondary analysis of archived data collected as part of formative qualitative work – using a group participatory ranking methodology (PRM) – informing research on the prevalence of GBV amongst IDPs in northern Uganda in 2006. Sixty-four PRM group discussions were held with women, with men, with girls (aged 14 to 18 years), and with boys (aged 14 to 18 years) selected on a randomized basis across four internally displaced persons (IDP) camps in Lira District. Discussions elicited problems facing women in the camps, and – through structured participatory methods - consensus ranking of their importance and narrative accounts explaining these judgments. Results Amongst forms of GBV faced by women, rape was ranked as the greatest concern amongst participants (with a mean problem rank of 3.4), followed by marital rape (mean problem rank of 4.5) and intimate partner violence (mean problem rank of 4.9). Girls ranked all forms of GBV as higher priority concerns than other participants. Discussions indicated that these forms of GBV were generally considered normalized within the camp. Gender roles and power, economic deprivation, and physical and social characteristics of the camp setting emerged as key explanatory factors in accounts of GBV prevalence, although these played out in different ways with respect to differing forms of violence. Conclusions All groups acknowledged GBV to represent a significant threat - among other major concerns such as transportation, water, shelter, food and security – for women residing in the camps. Given evidence of the significantly higher risk in the camp of intimate partner violence and marital rape, the relative prominence of the issue of rape in all rankings suggests normalization of violence within the home. Programs targeting reduction in GBV need to address community-identified root causes such as economic deprivation and social norms related to gender roles. More generally, PRM appears to offer an efficient means of identifying local constructions of prevailing challenges in a manner that can inform programming.